U.S. POINTER: Lessons learned about delivery of a multi‐domain lifestyle intervention during the COVID‐19 pandemic. (31st December 2021) - Baker, Laura D; Espeland, Mark A; Whitmer, Rachel A; Kivipelto, Miia; Antkowiak, Susan; Chavin, Melanie; Cleveland, Maryjo; Correia, Stephen; Day, Claire E; Elbein, Richard; Farias, Sarah Tomaszewski; Gitelman, Darren R; et al.
Abstract: Background: U.S. POINTER is testing whether multidomain lifestyle interventions focused on physical exercise, nutrition, cognitive challenge, and risk factor management reduces risk of cognitive decline in a heterogeneous population of at‐risk older adults in America. The study adapts the FINGER (Finnish Intervention Geriatric Study to Prevent Cognitive Impairment and Disability) interventions to fit the United States culture and delivers the intervention within the community at 5 sites across the country. Method: U.S. POINTER is a 2‐year RCT that will enroll 2000 cognitively unimpaired older adults who are at risk for cognitive decline due sedentary lifestyle, poor diet and other factors. Participants are randomized to one of two lifestyle intervention groups that differ in format and intensity. In 2020, the COVID‐19 pandemic presented a number of challenges for the study that affected recruitment, assessment schedules, and intervention delivery. Result: As of March 2020, when COVID‐19 incidence was on an exponential rise in the US, 240 participants had been enrolled in U.S. POINTER. In response to local and national safety mandates, study activities were paused from March 23 rd to July 13 th . During the pause, sites remained in contact with study candidates and enrolled participants to provide ongoing support to keep them engaged in the trial. Enrollees also received regular telephone calls to encourage continued adherence to their assigned lifestyle intervention. In response to the multiple pandemic‐related challenges, study protocols and procedures were adapted to facilitate and encourage participant adherence to intervention activities. At study re‐start, retention was 98%. Despite climbing COVID‐19 infection rates nationwide, enrollment at all 5 sites has continued at a steady rate (N=540 as of Jan2021), virtual Team Meeting attendance for both lifestyle groups exceeds 80%, and participants continue to successfully work toward their intervention goals. Conclusion: The COVID‐19 pandemic presented unprecedented challenges, but it also provided a unique opportunity to adapt intervention delivery so that a nonpharmacological community‐based trial could continue – even during a debilitating global health crisis. U.S. POINTER's adaptations to pandemic‐related challenges may ultimately increase the resilience of its interventions to even the most challenging of circumstances that older adults will face now and in the future.